Efforts to Improve Numeracy Skills by Fishing for Colorful Coral Stones at RA Perwanida Kutorejo Mojokerto - Prasetiya, Novita Aris; Sulistiawati, Sriana (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to improve children's numeracy skills through the use of colorful coral fishing media in Group A of RA Perwanida Kutorejo, Mojokerto. The background of this study is the low numeracy skills of children, particularly in recognizing numbers, counting objects, and matching numbers with the number of objects. This study used the Classroom Action Research (CAR) method with two cycles. Each cycle consisted of planning, action implementation, observation, and reflection. The subjects were 17 children in Group A aged 4–5 years. Data were collected through observation, field notes, and documentation, then analyzed descriptively using qualitative and quantitative methods. The results showed an increase in children's numeracy skills after being given the intervention using the colorful coral fishing media. Initially, most children still had difficulty counting correctly. After the intervention in Cycle I, children's numeracy skills began to improve, although not optimally. In Cycle II, children's numeracy skills improved significantly, with a success rate of over 80%. Therefore, it can be concluded that the use of colorful coral fishing media can improve children's numeracy skills in Group A of RA Perwanida Kutorejo.